P07 Improving the quality of diabetes care: exploring the perspectives of general practitioners in Ireland. (16th November 2010) - McHugh, S; O'Mullane, M; Perry, I J; Bradley, C P
Abstract : Objective: Health professionals are key players in the success or failure of quality management depending on their willingness to accept and adapt to changes in practice. The aim of this study was to explore GPs' experiences of providing diabetes care and their thoughts on the factors affecting its development. Design: Semi-structured qualitative interviews were conducted with GPs to explore their experience of care provision in Ireland, opinions on the factors influencing the development of care and their attitude to registration and audit. The topic guide was informed by the findings of a preceding national survey on the organisation of diabetes care. Analysis was conducted using a pragmatic approach drawing on the Framework method. Participants: A purposive sample of 30 GPs was selected based on 3 sets of inclusion criteria; (a) location (rural/urban), (b) computerised/non-computerised practice, (c) single-handed/group practice. Results: Preliminary analysis has identified both convergent and divergent themes. There were varying attitudes as to how diabetes care should be integrated between primary and secondary care settings. The locus of care varied across participant experiences from primary care-based management to supplementing hospital-led care. Lack of access to auxiliary services and resources were among the common barriers to an effective community-based diabetes service. Those GPs who have developed a structured approach to diabetes care tended to do so as a "labour of love"; most doing so without direct recompense. There were mixed attitudes towards the development of a national register with some questioning its use and benefit at a practice level. A number of GPs felt a national register should to be tailored to meet the needs of health professionals and patients, and not solely used as a research tool. There was ambivalence towards efforts to improve care based on previous experience in the Irish health setting. When asked about the future of diabetes care, GPs proposed regional diabetes management clinics and hoped for greater recognition of the contribution of general practice to diabetes care. Conclusion: Preliminary findings suggest there is a typology of care models in existence in Ireland with varying levels of involvement by GPs and diverse access to services. There were tentative attitudes towards quality improvement initiatives including the establishment of a register suggesting a sense of inertia towards organisational change. Extending high quality care to all patients with diabetes can no longer rely solely on the interest of care providers and may require commitment systems-level change.